2013
DOI: 10.1002/erv.2269
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Implications of High Levels of Autism Spectrum Disorder Features in Anorexia Nervosa: A Pilot Study

Abstract: Raw data on premature termination of treatment, despite no statistic impact, showed that seven out of the eight participants with high features of ASD completed treatment as planned compared with 50% of those with low ASD traits. Unexpectedly, this suggests enhanced treatment adherence in ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…In the Swedish cohort followed up over 30 years, participants with ASD traits were found to have a poorer global outcome (using Morgan and Russell scales) (Nielsen et al, 2015). Interestingly, this study found that although people with ASD engaged with treatment as much as non-ASD, the same was found in another adult inpatient sample (Huke, Turk, Saeidi, Kent, & Morgan, 2014) Interestingly, this study found that although people with ASD engaged with treatment as much as non-ASD, the same was found in another adult inpatient sample (Huke, Turk, Saeidi, Kent, & Morgan, 2014) …”
Section: Discussionmentioning
confidence: 56%
“…In the Swedish cohort followed up over 30 years, participants with ASD traits were found to have a poorer global outcome (using Morgan and Russell scales) (Nielsen et al, 2015). Interestingly, this study found that although people with ASD engaged with treatment as much as non-ASD, the same was found in another adult inpatient sample (Huke, Turk, Saeidi, Kent, & Morgan, 2014) Interestingly, this study found that although people with ASD engaged with treatment as much as non-ASD, the same was found in another adult inpatient sample (Huke, Turk, Saeidi, Kent, & Morgan, 2014) …”
Section: Discussionmentioning
confidence: 56%
“…This finding contrasts with the previously mentioned study of treatment completion in AN inpatients with high versus low ASD traits. In this earlier study a larger but non‐significant proportion of individuals with high ASD features were less likely to prematurely terminate their treatment than those with low ASD traits . The authors speculate that individuals with high ASD traits adopt and maintain the rules and routines imposed in an inpatient setting to ease anxieties of the new environment.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, a recent pilot study investigated treatment adherence in adult inpatients with AN who were divided into those with high or low ASD traits. A larger proportion of patients with high ASD traits completed treatment as planned compared with those with low ASD traits (high‐ASD 87.5%, low‐ASD 50%), although this effect did not reach statistical significance …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Unknown underlying ASD traits in AN may be an aggravating factor in certain psychological treatment modalities [31]. In the acute phase of AN, it is difficult to diagnose ASD accurately [22, 23].…”
Section: Discussionmentioning
confidence: 99%